OPTIMALISASI STRATEGI PEMASARAN UMKM MELALUI TWITTER: PERSPEKTIF LITERASI DIGITAL DAN NILAI ISLAMI - Rahmah, Zakiyah Zulfa; Sulistyowati, Sulistyowati (Politeknik Bisnis Indonesia, 2024)
The development of digital technology provides great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve competitiveness, especially through social media platforms such as Twitter. Twitter allows MSMEs to reach a wide audience, facilitate interactive communication, and optimize marketing costs. This research aims to explore MSME marketing strategies through Twitter by integrating digital literacy and Islamic values, such as shidq (honesty), amanah (trust), and ikhlas (sincerity). The method used is literature review, which analyzes various studies related to digital literacy, digital marketing, and sharia principles in business. The results showed that although Twitter has great potential as a marketing tool, MSME players still face challenges in digital literacy, especially related to content management and digital identity. The integration of Islamic values in digital marketing is proven to not only increase customer trust but also create long-term loyalty. In conclusion, Twitter can be a strategic tool for MSMEs to develop marketing that is transparent, interactive, and in accordance with Islamic principles. With the optimization of technology and the application of ethical values, MSMEs can develop sustainably in the midst of global market competition.